Reflection on an interprofessional communitybased participatory research project - A Rhoda; J Frantz; G Filies; K Jooste; M Keim; N Mlenzana; N Laattoe; N Roman; C Schenck; F Waggie (South African Medical Association, 2016)
Background. A collaborative interprofessional research project that involved community members was beneficial to community development.Objective. To draw upon the experiences of academics relating to their involvement in an interprofessional community-based participatory research(CBPR) project.Methods. A Delphi study was applied as a self-reflective evaluation process to reach consensus on the lessons learnt from participation in a CBPR project. Round one of the Delphi employed closed-ended questions and the responses were analysed descriptively using Microsoft Excel (USA). The second round consisted mainly of open-ended questions and responses, and was analysed qualitatively. Ethical clearance was obtained from the University of the Western Cape research committee.Results. Based on round one of the Delphi study, it became evident that recognition of the community as a unit of identity, addressing health from physical, emotional and social perspectives and formation of long-term commitments were the CBPR principles most applied. Disseminating information to all partners and facilitation of the collaborative equitable involvement of all partners in all phases of the research were the principles least applied. Themes that emerged from the second round of the Delphi included the identification of clear objectives based on the needs of the community, a shift from identification of the needs of the community to the implementation of strategies, and the creation of capacity-building opportunities for all stakeholders.Conclusion. In a reflection on the research process, the interprofessional team of academics found that the basics of CBPR should be attended to first. A focus on clear objectives, implementation strategies and capacity building is important in CBPR.